The Influence of the STAD (Student Team Achievement Division) Model on Student Learning Outcomes in Social Studies Subjects for Grade IV - Fitria, Wulan; Fauziah, Anna; Valen, Andri (Global Education Journal, 2025)
Education in elementary school is the instillation of a set of knowledge acquired by students through their learning experiences at school. This study aims to determine the effect of the STAD (Student Team Achievement Division) learning model on the learning outcomes of fourth-grade students in SD Negeri 64 Lubuklinggau. The research method used in this study is a quantitative approach with a pure experimental research method. The population is all fourth-grade students of SD Negeri 64 Lubuklinggau and the sample is class IV.B as an experimental class taken from the population. The data collection technique used in this study is a test. The data analysis technique used in this study is a normality test, a homogeneity test and a t-test. Based on the data analysis, it is known that the average learning outcomes of students in the experimental class are 80.33 and the control class is 63.94. Meanwhile, after being analyzed using the formula for the equality of two means (t-test) it shows that the t-table value is > t count (5.04 > 1.69) so it can be concluded that HO is rejected and Ha is accepted. So the hypothesis can be concluded that there is an influence of the STAD (Student Team Achievement Division) learning model on student learning outcomes in the Social Studies subject of Class IV of SD Negeri 64 Lubuklinggau.